Perbedaan Tingkat Nyeri Dada Sebelum dan Setelah Dilakukan Terapi Murottal Al-Quran - Priyanto Priyanto; Idia Indar Anggraeni (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2019)
Chest pain is a major complaint that is often felt by people with coronary heart disease. Chest pain occurs because of a decreased supply of oxygen to the myocardium. Murottal Al-Qur' therapy is a religious therapy where someone will be heard verses of Al-Qur’an for a few minutes so it will have a positive impact on one’s body, one of them is to reduce pain. This study aims to find out the difference between chest pain level before and after murottal Al-Qur'an therapy. This research design used a pre-experimental method with one group pre-test and post-test. The sampling method was accidental sampling, the number of sampling were 17 respondents. The research instrument used the Numeric Rating Scale to measure pain scale before and after murottal Al-Qur'an therapy, giving it once for 20 minutes. The test statistic used is the paired sample T-test. The results of this study indicate that there are significant differences in chest pain levels before and after murottal Al-Qur'an therapy with a p-value of 0.004 (p <α (0.05)).Murottal Al-Qur'an therapy can reduce the scale of a patient's chest pain. The need for socialization and application of murottal Al-Qur'an therapy in patients with chest pain. Keywords: Chest Pain, Murottal Al-Qur’an Therapy